1977
DOI: 10.1007/bf00582208
|View full text |Cite
|
Sign up to set email alerts
|

On the secretagogue effect of dibutyryl cyclic AMP in the rat exocrine pancreas

Abstract: DbcAMP greater than or equal to 0.1 mM induces the discharge of exportable enzymes from rat pancreas fragments incubated in vitro. This effect is qualitatively similar to the action of physiological secretagogues acting via hormone receptors: 1) it is accompanied by the appearance of exocytotic images at the acinar cell apex; 2) it is energy dependent but energy supply is low while that required for the carbamylcholine or caerulein response is high and can only be afforded by oxidative phosphorylation; 3) it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Consistent with this, it has been reported that the F-actin cytoskeleton in other cell types may consist of two distinct pools, one stable and the other dynamic (Fischer et al, 1998;Halpain, 2000;Ammar et al, 2001;Star et al, 2002). In pancreatic acinar cells F-actin remodelling is thought to occur in response to agonist stimulation, which demonstrates the need for a dynamic pool (Bauduin et al, 1975;Muallem et al, 1995;Valentijn et al, 2000); it is possible that a more stable F-actin pool plays a role in other cellular processes.…”
Section: Discussionsupporting
confidence: 55%
“…Consistent with this, it has been reported that the F-actin cytoskeleton in other cell types may consist of two distinct pools, one stable and the other dynamic (Fischer et al, 1998;Halpain, 2000;Ammar et al, 2001;Star et al, 2002). In pancreatic acinar cells F-actin remodelling is thought to occur in response to agonist stimulation, which demonstrates the need for a dynamic pool (Bauduin et al, 1975;Muallem et al, 1995;Valentijn et al, 2000); it is possible that a more stable F-actin pool plays a role in other cellular processes.…”
Section: Discussionsupporting
confidence: 55%
“…It has also become recognized that vasoactive intestinal polypeptide (VIP) and the hormone secretin, which act on target cells via cyclic AMP, as well as pharmacologic agents which increase cyclic AMP, such as cholera toxin, theophylline and 3-isobutyl-1-methyl xanthine, stimulate secretion in some species such as guinea-pig but not in others (Heisler, Grondin & Forget, 1974; Deschodt-Lanckman, Robberecht, DeNeef, Labrie & Christophe, 1975;Smith & Case, 1975;Bauduin, Stock, Launay, Vincent, Potvliege & Grenier, 1977;Gardner & Jackson, 1977;Robberecht, Deschodt-Lanckman, Lammens, DeNeef & Christophe, 1977;Gardner & Rottman, 1979). In mouse pancreas especially, agonists working via cyclic AMP have little or no effect on amylase secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon+CCK8 (8) of digestive enzymes from ducts by increased electrolyte secretion. In addition, reported effects of dibutyryl cyclic AMP (Morisset & Webster, 1971;Bauduin et al 1977) and phosphodiesterase inhibitors (Heisler et al 1974) on amylase release as evidence for the role of cyclic AMP iti enzyme secretion were questionable because of cell damage as indicated by excessive LDH release from acinar cells (Kempen et at. 1977).…”
Section: Resultsmentioning
confidence: 99%
“…Gardner & Jackson (1977) postulated that cyclic AMP (elaborated by acinar cells or contaminating duct cells) was involved in one of the major pathways for the regulation of digestive enzyme secretion from pancreatic acinar cells. In the rat pancreas, cholera toxin-induced increase in cyclic AMP was not accompanied by an increase in pancreatic enzyme secretion (Kempen, de Pont & Bonting, 1975;Smith & Case, 1975;Singh, 1979), whereas secretin, porcine VIP and exogenous derivatives of cyclic AMP increased pancreatic enzyme secretion (Robberecht, Deschodt-Lanckman, De Neef & Christophe, 1974;Heisler, Grondin & Forget, 1974;Deschodt-Lanckman, Robberecht, De'Neef, Labrie & Christophe, 1975;Kempen, de Pont & Bonting, 1977;Bauduin, Stock, Launay, Vincent, Potvliege & Grenier, 1977). The lack of enzyme secretion was noted in spite ofcholera toxin molecule being active biologically.…”
Section: Introductionmentioning
confidence: 99%